ETIKA BIROKRASI PADA BAGIAN PERUNDANG-UNDANGAN DI SEKRETARIAT DEWAN PERWAKILAN RAKYAT DAERAH KABUPATEN SIGI - Sukmawati, Mega (Katalogis, 2016)
Objectives to be achieved in this research is to identify and analyze ethical bureaucracy in Section Legislation in the Legislative Secretariat Sigi. This study refers to the opinion of the Ethics Bernhard Sutor bureaucracy that includes elements of Purpose, Means (modalities), and Action. This type of research in achieving the purposes and objectives of the research are descriptive method qualitative approach. The location of research in the Office of the Secretariat of the Regional Representatives Council Sigi District, and Time study will be conducted over three (3) months. Informants in this study were selected purposively as many as five people. Data collection techniques used were observation, interview, and documentation. The data analysis was performed with data reduction procedures, presentation of data and draw conclusions. The results of this study explains that the Ethics Bureaucracy On the Legislation in the Secretariat of the House of Representatives Sigi, overall not good, this is indicated on the three aspects of ethics used aspects of the objectives and aspects Facility (modalities) has been performing well, the aspect means (modalities) has been utilized properly. While aspects of the action not be in a good condition.